Diversification of Oyster Mushroom Products to Improve the Economy and Household Food Security - Ekalia Yusiana; Yeni Sari Wulandari; Siti Mariyani; Siti Latifatus Siriyah; Devie Rienzani Supriadi; Mohamad Sam'un; Abubakar; Slamet Abadi; Syifa Fauziah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Oyster mushroom is one of the important agricultural commodities cultivated by the community, especially in Kondang Jaya village, East Karawang District, Karawang Regency, West Java. In the hamlet of Griya Kondang Asri, Kondang Jaya village, oyster mushroom cultivation is carried out to empower women who are accommodated by the Berkah Farmer Women Group which has 20 local MSME groups. However, the implementation of mushroom cultivation is still not optimal because there are still many problems related to cultivation and there is no innovation in the management of oyster mushroom products, so people only sell oyster mushrooms in a fresh condition without packaging. Therefore, this service must be carried out. This activity aims to provide insight to the group of women farmers about mastering mushroom cultivation techniques, improving skills in creating and innovating nuggets and mushroom chips, as well as skills in making packaging designs, to increase the selling value of mushroom cultivation products of the Women Farmers Group. This activity was carried out using the Participatory Learning and Action (PLA) method. The result of the implementation of the service is an increase in the knowledge and skills of farmer group partners in utilizing mushroom crops in the diversification of products with high economic value.